2007
DOI: 10.1063/1.2768524
|View full text |Cite
|
Sign up to set email alerts
|

Ordering of lipid A-monophosphate clusters in aqueous solutions

Abstract: In this investigation, a study of the self-assembly of electrostatically stabilized aqueous dispersions of nanometric lipid A-monophosphate clusters from Escherichia coli was carried out in three different volume-fraction regimes. The experimental techniques used in the investigation were osmotic pressure, static and quasielastic light scattering, scanning electron microscopy and transmission electron microscopy, and small-angle x-ray scattering. Experiments were carried out at low ionic strength (I=0.1-5.0 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…At lower particle-number densities, as the length scale of the repulsive forces increased, the fluid-crystalline transition gave rise to BCC-type crystals. This implies that self-screening was much smaller than in previous studies and very different for Lipid A-monophosphate phases [38]. The experimental observations and the simulation support the existence of a transition from a fluid to a BCC structure rather than to an expected FCC structure for Lipid A-diphosphate clusters in e.g 5.0 mM NaCl.…”
Section: Freezing and Meltingsupporting
confidence: 51%
See 2 more Smart Citations
“…At lower particle-number densities, as the length scale of the repulsive forces increased, the fluid-crystalline transition gave rise to BCC-type crystals. This implies that self-screening was much smaller than in previous studies and very different for Lipid A-monophosphate phases [38]. The experimental observations and the simulation support the existence of a transition from a fluid to a BCC structure rather than to an expected FCC structure for Lipid A-diphosphate clusters in e.g 5.0 mM NaCl.…”
Section: Freezing and Meltingsupporting
confidence: 51%
“…8). The small cubic Pm 3 n (a = 6.35 nm) structure observed for the Lipid A-monophosphate clusters [38,48], but different form the large cubic unit cell with a = 49.2 nm materialized as a result of a space-filling combination of two polyhedra, a dodecahedra and a tetrakaidodecahedra. This is in contrast to the tetrakaidecahedra (Im 3 m) or rhombodo-decadecahedra (Fd3m) packings observed for the Lipid A-diphosphate assemblies.…”
Section: Packing Of Lipid A-phosphatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the interactions between colloidal particles like lipid A-monophosphate can be tuned by modifying either the particle surfaces or the properties of the ma- trix in which they are suspended. From recently obtained results, 35 it was found that the formation of nanocrystals of different shapes and sizes was a function of the volume fraction. The ordering of charged lipid A-monophosphate clusters in aqueous dispersions at low ionic strength was also indicated.…”
Section: Introductionmentioning
confidence: 97%
“…However, if the volume fraction was increased the dispersions became iridescent. 35 In fact, the iridescence resulted from the formation of lipid A-monophosphate colloidal crystals in the size range from ϳ10 nm to 1 m. Understanding the growth phenomenon is of major interest, not only because of a gain in insight into cluster-cluster interactions, 36 but also from a structural point of view. Thus, with an understanding of these features, there is a possibility of growing suitable single crystals, which may be used in detailed structural analyses.…”
Section: Introductionmentioning
confidence: 99%